Peran mediasi brand experience terhadap pengaruh user-generated social media communication pada customer-based brand equity - Haidar, Safiradinda; Fachrunnisa, Olivia (Universitas Widya Mataram, 2025)
The increasingly tight competition in the telecommunications industry, has encouraged companies to have a unique position in the minds of customers. This study aims to analyze the role of brand experience mediation in influencing user-generated social media brand communication towards brand customer-based brand equality on the Indibiz Telkom Instagram platform. The research design was cross-sectional, with a sample of 170 respondents from Indibiz Telkom customers and social media followers. Data were collected through questionnaires and analyzed using Smartpartial Least Square (SmartPLS). The results of the study showed that user-generated social media brand communication had a significant effect on brand experience (p = 0.000; β = 0.749; t> 1.96) but did not have a significant direct effect on customer-based brand equity (Y) (p = 0.264; β = 0.116; t <1.96). Brand experience (Z) has a significant influence on customer-based brand equity (Y) (p = 0.000; β = 0.761; t > 1.96) and plays a key role in mediating the relationship between user-generated social media brand communication and customer-based brand equity (p = 0.000; β = 0.570; t > 1.96). This shows that Brand Experience, which includes sensorial, emotional, intellectual, and behavioral experiences, is an important element in increasing customer-based brand equity. Model provides a new theoretical understanding of the dynamics of brand communication on digital platforms, which can be useful if applied.